Proposed business strategy for raga studio - Krisnaldi Mahdi, Amanda; Kusumo Bintoro, Bambang Purwoko (The Indonesian Journal of Business Administration, 2018)
Abstract – Humans can do their daily activities effectively and feel happier with a healthy body and mind. Health would be categorized as something that is expensive if humans do not have good health and often get sick. Therefore, more awareness is needed to maintain and improve the health of body. To keep body to stay healthy, humans are encouraged to live a healthy lifestyle. Furthermore, health and fitness centers market also grows nowadays. Realizing this opportunity, Raga Studio as a fitness group class provider, has a big opportunity to grab many members. However, Raga Studio is facing lack of business strategy, fierce competition, and human resources inefficiency. This fitness studio has to solve and overcome these problems in order to generate more revenue and face challenges in the future. In order to overcome the aforementioned problems, appropriate business strategies and recommended business model are formulated. Afterwards, the implementation plan that allows Raga Studio to obtain information regarding the suggested activities and monitor its performance is needed. The plan will be focused in improving the quality of the service offerings, maintaining relationship with customers and employees, and also expanding potential market and partnership. Keywords: business model canvas, business strategy, fitness industry, TOWS matrix